Social enhancement of fitness in yellow-bellied marmots - Armitage, Kenneth B. (The National Academy of Sciences, 2000)
The yellow-bellied marmot (Marmota flaviventris) is a social, ground-dwelling squirrel that lives either individually or in kin groups of from two to five adult females. Philopatry and daughter recruitment lead to the formation and persistence of matrilines at habitat sites. By using 37 years of demographic data for 12 habitat sites, we could determine long-term trends in the effects of group size on two measures of fitness, survivorship and net reproductive rate, which otherwise are obscured by annual fluctuations in these measures. Both size and number of matrilines varied among sites and survivorship and net reproductive rate varied among sites and among matriline sizes. The role of social organization was explored further by examining the effect of matriline size, averaged over all years and sites, on fitness. For both survivorship and net reproductive rate the relationship with matriline size was curvilinear. Fitness increased with the increase in matriline size and then decreased in the largest groups. Decreased fitness in matrilines of four or five was associated with agonistic behavior, a large number of 2-year-old females in the social group, and reproductive suppression. There is no evidence that females acted to increase their fitness by increasing indirect fitness; i.e., by assisting relatives, but attempted to increase direct fitness. Direct fitness increased when mortality and fission of large matrilines reduced group size and the surviving females increased reproduction.